New-onset Diabetes Mellitus among adults as sequelae of COVID-19 in selected tertiary care hospital, Puducherry – A cohort study - Venkatachalam Jayaseelan; Sitanshu Sekhar Kar; Mahadevan Duraiswamy; Manju Rajaram; Vikas Menon; Mukta Wyawahare; D.R. Veda Priya; Ravivarman Lakshmanasamy; Vanessa Ravel; Renjana Sivaji (Clinical Epidemiology and Global Health)
Background: Diabetes Mellitus is one of the most common comorbidities in patients with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). However, data on the incidence of Diabetes Mellitus among adults as post-COVID sequelae has been limited, and this study aims to determine the incidence and the associated factors of Diabetes Mellitus among adults who had COVID-19 infection. Methods: This prospective cohort study was carried out among COVID–19 symptomatic (moderate and severe) and asymptomatic cases admitted or reported in a tertiary care hospital in Puducherry, India. Participants were recruited between May and December 2022. It includes socio-demographic details and follow-up data on clinical symptoms and blood sugar levels for 724 participants without a prior history of Diabetes Mellitus, with 362 in the exposed group and 362 in the comparison group for incidence of Diabetes Mellitus, followed-up for 3 months. Results: Among the study participants, the relative risk of developing Diabetes Mellitus was 2.83 (95 % CI: 1.98–4.06) for the exposed group (moderate/severe cases) compared to the comparison group (mild/asymptomatic). Multivariable analysis further confirmed a relative risk of 2.01 (95 % CI: 1.26–3.20, p = 0.003) for moderate/severe COVID-19 cases, with significant associations for age, smoking, and comorbidities. Conclusion: By the 3rd month, new-onset Diabetes Mellitus was significantly higher in moderate to severe COVID-19 cases. Older age, smoking, and comorbidities were key factors. These findings highlight the need for closer monitoring of severe COVID-19 patients for new-onset diabetes in the post-COVID period.